Pengembangan LKPD Kimia Materi Asam Basa Berbasis Problem Based Learning untuk Menumbuhkan Pemahaman Konsep Siswa - Khairi Alfiana; Mukhtar Haris; Sunniarti Ariani (Chemistry Education Practice, 2026)
This study aims to test the level of validity and practicality of the Chemistry Student Worksheet on acid-base material based on problem-based learning to foster students' conceptual understanding. The research method used is Research and Development (R&D) with a 4D development model that includes the stages of define, design, development, and disseminate. The subjects of this trial were lecturers of Chemistry Education FKIP University of Mataram and chemistry teachers of SMAN 1 Labuhan Haji for the purposes of validating the worksheet and 66 students of grades XI Health I and XI Health II for the purposes of testing the practicality of the worksheet. The data collection technique used was a questionnaire. The data analysis technique used the Aiken's V formula and the percentage of practicality. The results showed that the Chemistry Student Worksheet on acid-base material based on problem-based learning to foster students' conceptual understanding that had been developed by this researcher obtained an average validity of 0.89 in the very valid category and an average practicality value of 83% in the very practical category. Thus, it can be concluded that the chemistry student worksheet (LKPD) for acid-base matterl based on Problem Based Learning is suitable for use as teaching material to help foster students' conceptual understanding and support an active and meaningful learning process.